Higher Effective Oronasal versus Nasal Continuous Positive Airway Pressure in Obstructive Sleep Apnea: Effect of Mandibular Stabilization - M Kaminska; A Montpetit; A Mathieu; V Jobin; F Morisson; P Mayer (Canadian Respiratory Journal)
BACKGROUND: In some individuals with obstructive sleep apnea (OSA), oronasal continuous positive airway pressure (CPAP) leads to poorer OSA correction than nasal CPAP. The authors hypothesized that this results from posterior mandibular displacement caused by the oronasal mask.